2020
DOI: 10.21203/rs.3.rs-42505/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics and Outcome of Patients With Covid-19 in Sri Lanka; An Observational Study

Abstract: Background Clinical manifestations of coronavirus disease 2019 (COVID19) can vary from asymptomatic to profusely symptomatic due to many factors. Having data on the clinical characteristics of the affected patients is important for the screening and diagnosis of COVID-19. Main objective of this study is to evaluate the clinical and epidemiological characteristics and outcomes of patients with COVID-19 admitted to six treatment centres in Sri Lanka. Methods For the specific epidemic situation of COVID-19, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Another characteristic feature of our patients was loss of smell or taste. But this was only reported from Sri Lanka with a lower rate [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another characteristic feature of our patients was loss of smell or taste. But this was only reported from Sri Lanka with a lower rate [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 85%
“…This is consistent with a summary report of 72,314 cases from China 15 . The severity of COVID-19 at presentation was not clearly mentioned in the early reports from the South Asian countries [11][12][13][14] . Most of the literature described the severity of illness among hospitalized patients.…”
Section: Discussionmentioning
confidence: 94%
“…The mean or median age of subjects in the 104 studies ranged from 26 to 77 years. Studies reported on subjects from multiple countries (n = 5), 15−19 Australia (n = 1), 20 Belgium (n = 1), 21 Brazil (n = 1), 22 Canada (n = 2), 23,24 China (n = 7), 2,19,25−29 France (n = 12), 19,30−39 Germany (n = 10), 19,40−46 Greece (n = 1), 49 Iceland (n = 1), 50 India (n = 2) 51,52 Iran (n = 3), 53−55 Iraq (n = 2), 56,57 Israel (n = 4), 58−61 Italy (n = 19), 62−80 Japan (n = 1), 81 Korea (n = 3), 82−84 the Netherlands (n = 1), 85 Poland (n = 1), 86 Qatar (n = 1), 87 Singapore (n = 2), 88,89 Spain (n = 6), 90−95 Sri Lanka (n = 1), 96 Sweden (n = 1), 97 Switzerland (n = 1), 98 Taiwan (n = 1), 99 Turkey (n = 4), 100−103 the U.K. (n = 3), 104−106 and the U.S.A. (n = 9). 104,107−114 The overall estimated random prevalence of smell loss among COVID-19 patients, calculated from a total of 91 studies containing 25 750 patients, was 43.04% [95% confidence interval (CI), 36.39−49.96%].…”
Section: ■ Resultsmentioning
confidence: 99%
“…The mean or median age of subjects in the 104 studies ranged from 26 to 77 years. Studies reported on subjects from multiple countries ( n = 5), Australia ( n = 1), Belgium ( n = 1), Brazil ( n = 1), Canada ( n = 2), , China ( n = 7), ,, France ( n = 12), , Germany ( n = 10), , Greece ( n = 1), Iceland ( n = 1), India ( n = 2) , Iran ( n = 3), Iraq ( n = 2), , Israel ( n = 4), Italy ( n = 19), Japan ( n = 1), Korea ( n = 3), the Netherlands ( n = 1), Poland ( n = 1), Qatar ( n = 1), Singapore ( n = 2), , Spain ( n = 6), Sri Lanka ( n = 1), Sweden ( n = 1), Switzerland ( n = 1), Taiwan ( n = 1), Turkey ( n = 4),…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported anosmia prevalence in eighteen cohorts with a total of 7,247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait and Singapore [42][43][44] and twelve from India or Pakistan. [45][46][47][48][49][50][51][52][53][54][55][56] We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9,626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table 1, illustrated in Fig. 3A, B).…”
Section: Systematic Review and Meta-analysis Of South Asian Studiesmentioning
confidence: 99%